2023
DOI: 10.1292/jvms.23-0088
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and homology of the caudal auricular muscles in greater short-nosed fruit bat (<i>Cynopterus sphinx</i>)

Abstract: Bats can be phylogenetically classified into three major groups: pteropodids, rhinolophoids, and yangochiropterans. While rhinolophoids and yangochiropterans are capable of laryngeal echolocation, pteropodids lack this ability. Delicate ear movements are essential for echolocation behavior in bats with laryngeal echolocation. Caudal auricular muscles, especially the cervicoauricularis group, play a critical role in such ear movements. Previously, caudal auricular muscles were studied in three species of bats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…To visualize the cartilage and muscle for postnatal individuals (P0, 14, 21, 30, 45, and adult), the diffusible iodinebased contrast-enhanced CT technique [51] was conducted. This method has been shown to effectively allow us to non-destructively investigate the morphology of bat soft tissues in detail [36,37,[85][86][87][88]. Specimens were stained with 1% iodine in ethanol for at least 48 hours and up to 14 days.…”
Section: Three-dimensional Reconstruction Of Hyolaryngeal Morphologymentioning
confidence: 99%
“…To visualize the cartilage and muscle for postnatal individuals (P0, 14, 21, 30, 45, and adult), the diffusible iodinebased contrast-enhanced CT technique [51] was conducted. This method has been shown to effectively allow us to non-destructively investigate the morphology of bat soft tissues in detail [36,37,[85][86][87][88]. Specimens were stained with 1% iodine in ethanol for at least 48 hours and up to 14 days.…”
Section: Three-dimensional Reconstruction Of Hyolaryngeal Morphologymentioning
confidence: 99%
“…The 3D reconstruction of adult C. sphinx previously reported by Chi et al . [ 5 ] is shown in Fig. 3
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…1 , 2 , and 3 ). We previously reported three cervicoauricularis muscles in the common ancestor of laurasiatherians [ 5 ]. Other studies have reported four muscles in rhinolophoid bats [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations